Self-medication by elderly persons of seniors’ clubs in Valparaiso (Chile) - Vergara, Waldo; Armijo, Jorge; Solís, Gilda; Campalans, Eliette; Moya, Yanneth (Revista Chilena de Salud Pública, 2014)
Introduction: Self-medication in elderly patients can be an important public health problem, especially since it can affect concomitantly taken prescribed medications. Aims: To determine the prevalence and factors associated with medication use without a prescription elderly persons of Valparaiso, Chile. Materials and Methods: Prospective, descriptive study carried out in a group of 357 elderly persons belonging to seniors’ clubs in Valparaiso. Results: We found self-medication at a prevalence of 83.0%. The most common reason stated was "I do not like going to the doctor" (24%). Pain was the main condition for which individuals self-medicated. Importantly, self-medication using alternative medicine was detected in this group of patients. Despite 88.2 % of patients claiming to know the action of the drug, 49.3% say they require help to choose the medicines with which to self-medicate. Conclusions: These results suggest an opportunity for the health team to provide education with respect to pathology and medicines. In addition, it highlights the responsibility required to ensure responsible drug marketing so that it is orients consumers to self-medicate responsibly